Dynamically Induced Excitonic Instability in Pumped Dirac Materials. Issue 2 (29th January 2020) - Pertsova, Anna; Balatsky, Alexander V.
Abstract: Driven and non‐equilibrium quantum states of matter have attracted growing interest in both theoretical and experimental studies in condensed matter physics. Recent progress in realizing transient collective states in driven or pumped Dirac materials (DMs) is reviewed herein. In particular, the focus is on optically pumped DMs which are a promising platform for transient excitonic instabilities. Optical pumping combined with the linear (Dirac) dispersion of the electronic spectrum offers a knob for tuning the effective interaction between the photoexcited electrons and holes, and thus provides a way of reducing the critical coupling for excitonic instability. As a result, a transient excitonic condensate could be achieved in a pumped DM while it is not feasible in equilibrium. A unifying theoretical framework is provided for describing transient collective states in 2D and 3D DMs. The experimental signatures are described and numerical estimates of the size of the dynamically induced excitonic gaps and the values of the critical temperatures for several specific systems, are summarized. In addition, general guidelines for identifying promising material candidates are discussed. Finally, comments are provided regarding recent experimental efforts in realizing transient excitonic condensate in pumped DMs, and outstanding issues and possible future directions are outlined. Abstract : A recent proposal for transient excitonic condensate in optically pumped Dirac materials is reviewed in the context of a broader search for dynamically induced quantum states of matter. A unified theoretical framework for describing transient excitonic states in 2D and 3D Dirac materials is developed and model predictions for real materials are analyzed within this common framework.